Towards Non-standard Language Phenomena in Old Czech Texts - Svobodová, Andrea; Voleková, Kateřina (Bohemica Olomucensia, 2016)
When interpreting the Old Czech graphic records in manuscripts from 14th and 15th centuries, it is necessary to consider a massive development in all language levels of the Old Czech on one hand and on the other hand a vacillation and disunity of the ortography. Non-standard phenomena in Old Czech manuscripts refers to deviations from normal contemporary written records, which might be evaluated by the authors of historical grammars in a different way, secondly as phenomena caused by inappropriate scribal analogy, partly as a reflection of dialectal origin of the author or the scribe. However today, in the context of the predominant form of transcribed edition appears besides the question of classification of these non-standard phenomena also the question of its transcription. Recently in the Department of Language Development of the Institute of the Czech Language of the Academy of Sciences of the Czech Republic, v. v. i., are produced transcribed editions of several Old Czech texts considered Moravian (Sermon based on legends, Dzikowian sermons, Lviv anthology of prayers and legends, Ostrihom dictionary) for needs of the Editorial module and Text bank of Vokabulář webový; nevertheless as there are no generally accepted principles of transcription, the approaches varies by individual editors. This situation implies the urgent need to compile uniform transcription rules rising from the inventory of problematic phenomena that needs to be built and continuously updated. The paper should at least in general outline the most frequent non-standard phenomena and try to grasp them in terms of historical dialectology.
Keywords: Old Czech; historical dialectology; non-standard language phenomena; transcription; ortography